Aspired managerial styles of Muslim employees in Malaysia - Juhdi, Nurita; Wan Jusoh, Wan Jamaliah; Supar, Norizah (2014)
The aim of study was to examine the aspired managerial styles of Muslim managers and future managers in Malaysia. The employees who participated in the survey were all Muslims, aged 45 years and below, performing professional occupations or in middle to higher level positions (lowest position was administrative executive) in various organizations in Malaysia. They also had gone through some extent of development programs like mentoring, managerial/leadership courses and on-the-job experiences in administration or management. Data were collected using survey forms that contained items that measured studied variables. One thousand survey forms were distributed to employees who meet the criteria and the data collection was conducted in several states in Malaysia. As a result, a total of 413 forms were received but quite a number of forms were poorly responded and thus only 399 were used for further analysis. The factor analysis produced 7 factors which were then labelled as “altruistic”, “goal-oriented”, “consultative”, “innovative”, “practical”, “delegating” and “moral-based”. The cronbach’s alpha of each factor was between .616 and .797. The mean values of the individual items ranged from 3.20 to 4.18. In fact, only one item (i.e. behave in accordance with my religious belief) with the mean value of 4.18 and all the rest were rated below 4. The very moderate mean values indicated several concerns. It could be the lack of understanding of the employees about their roles as managers, or their hesitance to visualize what kind of managers they will be in the future. Worse, it could be the quality of management development programs they have participated. The overall findings gave some insights for HR practitioners in the area of talent development and management among future managers in organizations.